Fundamentals of Sustainable Urban Design. - Friedman, Avi (Springer, 2021)
This book begins with an introduction describing current societal transformations that merit new urban designs, including depletion of non-renewable natural resources, elevated levels of greenhouse gas emissions, large numbers of aging “Baby Boomers,” and climate change. Friedman then examines these challenges through thirty chapters of interest to urban designers, architects, civil and construction engineers, and town planners. Each of these topics represents an aspect of urban design and describes an innovative solution and offers a detailed description of underlying principles. The highly illustrated text presents innovative urban design strategies based on sustainable principles. Integrated with each chapter are several international case studies illustrating design implementations.
Keywords: Stadtgestaltung; Siedlungsgestalt; Baugestaltung; Städtebauliche Anlage; Verkehrsraum; Stadtverkehrsplanung; Öffentlicher Raum; Grünraum; Stadtgrün; Flächennutzung; Lehrbuch